Range assignment of protons in 18-oxygenated dosimetry gel using MR-PET imaging. (September 2016) - Runz, M.; Runz, A.; Mann, P.; Witte, M.; Jäkel, O.
Abstract : Introduction: When treating patients in radiation therapy with heavy ions the produced radioactivity can be used to determine particle ranges and/or the agreement with the target volume to be irradiated using positron emission tomography (PET). We present a method that combines dosimetry and PET data to verify proton ranges using phantom measurements. Purpose: Qualitative methods for the determination of proton energy range using a combination of polymer gel dosimetry and PET. Materials and methods: Polymer dosimetry-gel (PAGAT) was used to produce a radiation-induced polymerization which can be measured by magnetic resonance imaging (MRI). An additional enhancement of 21.75% of dosimetry-gel with oxigen-18 produces fluorine-18 by means of nuclear reaction with proton irradiation at the Heidelberg Ion-Therapy -Center (HIT) which can be measured with PET. The structure was tested for different kinds of beam applications: (i) pencil beam, (ii) pencil beam scanning and (iii) spread-out Bragg peak. Combined measurements were carried out on a MR/PET hybrid imaging device at the DKFZ. Results: MRI analysis and calculations showed good compliance with respect to beam shape and energy range. The location of dose enhancement could be verified with PET. Due to the low resolution, however, no precise statements about the beam shapes and ranges could be made. Conclusion: Oxygen-18 enriched PAGAT gels can be used to combine standard dosimetry gel evaluation and PET measurements. They showed a significant F-18 increase at the high dose area of MRI data. Improvements in the detection of beam shape and range can be realized using a small animal PET and/or by increasing the Oxyen-18 concentration.